INTERNET PADA INDUSTRI PARIWISATA - Luki Adiati Pratomo (Universitas Trisakti, 2001)
In the recent years, the Internet is growing very fast. And tourism as one of the service industry already used it extensively. This article will discuss the growing interest of Internet usages in the tourism industry, especially in the hotel industry. It will explore how the hotel industry maximizes e-propit and minimize e-cost and what is the hotel preparation for using the Internet as they marketing tools.